Design and Implementation of Point to Point Wireless Network with VPN IPSec and GRE Security for Internet Network Distribution in Sulangai Village - Wiranata, Agus Budiman; Sasmita, Gusti Made Arya; Raharja, I Made Sunia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Udayana, 2024)
Sulangai Village experiences limited internet access due to its geographical condition in a mountainous area, so cable infrastructure such as fiber optics is difficult to implement. The proposed solution is to use point-to-point wireless networks to provide reliable internet access. The research method used is the Network Development Life Cycle (NDLC), including the stages of analysis, design, simulation, implementation, monitoring and management. The test results show that the signal strength at the Base Station and Client Station is -69 dBm each, which is in the very good category. Security testing using IPsec VPN and GRE also showed adequate results, with the ability to encrypt data and protect the network from outsiders. Bandwidth speed testing before and after security implementation shows stable and satisfactory network performance, with consistent transmission and reception speeds. The results of the Quality of Service (QoS) analysis also show a significant increase after implementing security, with good throughput, packet loss, delay and jitter values.